2011
DOI: 10.1111/j.1439-0396.2011.01135.x
|View full text |Cite
|
Sign up to set email alerts
|

A krill oil supplemented diet reduces the activities of the mitochondrial tricarboxylate carrier and of the cytosolic lipogenic enzymes in rats

Abstract: The mitochondrial tricarboxylate carrier supplies cytosol with the carbon units necessary for hepatic lipogenesis. The activities of cytosolic acetyl-CoA carboxylase and fatty acid synthetase are therefore strictly connected to the function of mitochondrial tricarboxylate carrier. Dietary polyunsaturated fatty acids (PUFA) are potent modulators of hepatic lipogenesis. In rats fed with a diet enriched with 2.5% krill oil (KO), a novel source of dietary n-3 PUFA, a time-dependent decrease in the activities of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
36
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 47 publications
8
36
0
Order By: Relevance
“…Similarly to the present study (Figure 2), FO in the rat diet decreased plasma TC also in most of the recent studies (Lu et al 2011;Takahashi 2011;Campioli et al 2012;Ferramosca et al 2012;Xiao et al 2012). However, Yamazaki et al (2011) and Campioli et al (2012) did not find differences in TC between the FO-fed rats and the control rats.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Similarly to the present study (Figure 2), FO in the rat diet decreased plasma TC also in most of the recent studies (Lu et al 2011;Takahashi 2011;Campioli et al 2012;Ferramosca et al 2012;Xiao et al 2012). However, Yamazaki et al (2011) and Campioli et al (2012) did not find differences in TC between the FO-fed rats and the control rats.…”
Section: Discussionsupporting
confidence: 90%
“…Plasma cholesterol. Plasma TC level of the FOfed rats in the present experiment (1.07 mmol/l; Figure 2) is approximately in the middle of the range of the results of similar experiments (FO-fed rats; all data recalculated to mmol/l): 3.22 (Lu et al 2011) → 2.45 (Ferramosca et al 2012) → 2.36 (Xiao et al 2012) → 2.04 (Campioli et al 2012) → 1.01 (Yamazaki et al 2011) → 0.98 (Takahashi 2011) → 0.54 (Popovic et al 2011).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…A recent study comparing the bioavailability of PL and TAG in the form of krill oil and fish oil in healthy subjects demonstrated increased levels of EPA and DHA in plasma and red blood cells (RBC) after four weeks of krill oil intake compared to fish oil [8]. In addition, animal studies have shown a more efficient reduction in plasma lipid levels with PL compared to TAG intervention [9]. Herring roe oil supplementation has shown promising results in animal studies, including reduction in plasma lipids and inflammatory parameters, and improved insulin sensitivity [10,11].…”
Section: Introductionmentioning
confidence: 99%